Isolasi dan Identifikasi Secara Molekuler Ganoderma spp. yang Berasosiasi dengan Penyakit Busuk Pangkal Batang di Kelapa Sawit - Maria Indah Purnamasari; Cahya Prihatna; Agustin Wydia Gunawan; Antonius Suwanto (Jurnal Fitopatologi Indonesia, 2012)
A number of Ganoderma spp. isolates was isolated from oil palms attacked by basal stem rot (BSR) disease in Padang and Pontianak plantations. Genetic polymorphism of these isolates was analyzed based on the internal transcribed spacer (ITS) sequence of ribosomal DNA region. In addition, a restriction fragment length polymorphism (RFLP) analysis was also performed to determine the association of the isolates with BSR disease. The isolated Ganoderma spp. showed high DNA polymorphism and there was no obvious genetic clustering of isolates that may correspond to their geographical position in Padang and Pontianak. This indicated that exchange of DNA between Ganoderma spp. infecting oil palm is not uncommon. This can be explained by the heterothallic nature of Ganoderma spp. in which DNA recombination occurs during sexual reproduction between different thalli. RFLP analysis showed that ITS fragments from all Ganoderma spp. isolates were digested with restriction enzymes MluI and SacI. This indicated that the anoderma spp. isolates were specific for oil palm and thus associated with the BSR.Key words: basal stem rot, Ganoderma spp., internal transcribed spacer, oil palm